The global west : connections & identities - Frank Kidner; Maria Bucur; Ralph W. Mathisen; Sally McKee; Theodore R. Weeks (Australia : Cengage, 2019)
Intimidated by the thought of taking Western civ? You may be in for a pleasant surprise because THE GLOBAL WEST isn't a typical Western civ textbook. Developed by authors who've spent years helping a diverse range of students understand history, the book uses stories of ordinary people and their impact on history, along with stunning images and maps that make the subject interesting. You'll also have lots of help learning concepts with learning objectives, an easy-reading narrative and a clear message that helps you "get" the origins of today's interconnected world.
Keywords: textbook; history